2008
DOI: 10.1080/00480169.2008.36821
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive analysis of the foot lesions identified during veterinary treatment for lameness on dairy farms in north Taranaki

Abstract: This study provides baseline data with which veterinarians can compare their results to identify significant patterns on specific farms, which will suggest specific causal factors for lameness on those farms and thus better guide prevention programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…White-line disease is probably more diffi cult to treat than sole injury (Chesterton et al 2008). However, this study found no signifi cant impact of lesion type on the response of the nociceptive threshold to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…White-line disease is probably more diffi cult to treat than sole injury (Chesterton et al 2008). However, this study found no signifi cant impact of lesion type on the response of the nociceptive threshold to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A later study showed that the use of NSAID could signifi cantly reduce the duration of this hyperalgesia; 3 days of treatment with a short-acting NSAID, ketoprofen, resulted in a signifi cant increase in nociceptive threshold over a 28-day period (Whay et al 2005). The direct relevance of these studies to the New Zealand situation is unclear as the aetiology and pathogenesis of lameness in dairy cows in New Zealand are markedly different from those in the UK (Laven and Lawrence 2006;Chesterton et al 2008), as is the management of cows. This study was thus designed to evaluate the effect of lameness on nociceptive threshold under New Zealand conditions, and to assess the effectiveness of current lameness treatment regimes in reducing the hyperalgesia associated with lameness.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Only limited changes were made that refl ected differences in cattle practice between the UK and New Zealand. For example, questions relating to digital dermatitis and sole ulcer, both of which are far less common in New Zealand than in the UK (Chesterton et al 2008), were replaced with questions about white-line disease and footrot.…”
Section: Methodsmentioning
confidence: 99%
“…It is considered to be one of the most important health, welfare and economic problems in the New Zealand dairy industry (Chesterton et al 2008;Laven and Holmes 2008). The main environmental factors associated with the incidence of lameness in New Zealand herds are farm and herd size, animal handling and management practices (Chesterton et al 1989).…”
Section: Introductionmentioning
confidence: 99%